Cross-cultural Communication as A Basic Part Of Teaching Foreign Language - Turgunova Muqaddas Tursunbayevna (Genius Journals, 2022)
In given article there is considered about cross-cultural communication as the main part of to study the foreign languages. Cross-cultural communication - a relationship and contact between representative of the different cultures that expects as direct contacts between people and their generality, so and mediated forms of communications including language, speech, system of writing, electronic communication. In the article there is also studied some main notions of cross-cultural communications.
Keywords: communication; information; language; culture